Environmental Pollution and Threats to the Future of Sustainable Ecotourism: Challenges and Solutions in Riau Province - Sadad, Abdul; Zulkarnaini, Zulkarnaini; Nasution, Mimin Sundari; Mayarni, Mayarni (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2024)
Riau Province has great potential in ecotourism development, especially in coastal areas, mangrove forests, and tropical peatlands. However, this development is faced with serious challenges in the form of environmental pollution that threatens the sustainability of natural tourism destinations. This study aims to identify the forms of pollution that occur in Riau's ecotourism areas, analyze their impacts on ecosystems and tourism activities, and formulate strategic solutions for sustainable management. The method used is a qualitative approach with case studies in several leading ecotourism locations such as Mangrove Ecotourism in Bengkalis and Zamrud Lake tourism in Siak. Data were collected through interviews, observations, and field documentation. The findings of this study clearly demonstrate that environmental pollution—particularly from domestic waste, peatland fires, and land-use changes—poses a significant threat to the ecological integrity and long-term viability of ecotourism destinations in Riau Province. Without immediate and coordinated intervention, these threats risk undermining the region’s ecotourism potential. Therefore, this study concludes that sustainable ecotourism in Riau can only be achieved through an integrative and participatory management model that involves capacity building for local communities, strict enforcement of environmental regulations, and multi-stakeholder collaboration. Such strategic efforts are essential to preserve the natural assets of Riau and ensure that ecotourism continues to provide ecological, social, and economic benefits in the future.